Embeddedness levels in Central and East European countries as revealed by patent-related indicators. (1st December 2014) - Inzelt, Annamária
Abstract : Central and East European countries (CEECs) still show many features of the Soviet era. Consequently, the region seems, in several ways, to have been shaped by a single universal phase of transformation. This explains, at least in part, the relatively weak patenting activities and innovation performance of these countries. This paper deals with quantitative information originating from a newly created databank and investigates CEECs, employing various patent indicators in a Triple Helix context. New member states of the European Union (EU) from CEECs accounted for less than 1% of European patents between 1990 and 2006. This figure does not improve if patent applications are normalised according to population, and the number of patents registered in the region has evolved very little over the years. Analysing the relationships among old and new member states of the EU and their regions in terms of citations shows the pattern of intellectual linkages within Europe quite clearly. Even if CEECs feature relatively rarely in cited European publications, there are still 43 CEE affiliations recorded among the top 500 in Europe (ranked by performance). Intellectual linkages are still weak (both within the CEE area and among old and new EU member states and their regions), and the citation pattern clearly shows the importance of externally derived knowledge for CEE countries. Self-citation highlights the weakness of scientific impulses from the immediate environment to patenting activity. A very low level of self-citation may be indicative not only of low capabilities in terms of knowledge production, but also of a basic weakness in knowledge dissemination and absorption. In this respect, CEE universities have not yet shown themselves to be strongregional innovation organisers.